Peripheral Cytokines as a Chemical Mediator for Postconcussion Like Sickness Behaviour in Trauma and Perioperative Patients: Literature Review - Yasir Rehman; Nadia Rehman; Riaz Rehman (Neurology Research International)
Besides brain injury and systemic infection, cognitive and concussion like sickness behaviour is associated with muscular trauma and perioperative patients, which represents a major obstacle to daily activities and rehabilitation. The neuroinflammatory response triggers glial activation and consequently the release of proinflammatory cytokines within the hippocampus. We review clinical studies that have investigated neurocognitive and psychosomatic symptoms related to muscular trauma and in perioperative conditions. These include impaired attention and executive and general cognitive functioning. The purpose of this literature review is to focus on the systemic inflammation and the role of proinflammatory cytokines IL1, IL6,and TNF and other inflammatory mediators which mediates the cognitive impairment and induces sickness behaviour. Moreover, this review will also help to determine if some patients could have long-term cognitive changes associated with musculoskeletal injuries or as a consequence of surgery and thereby will lead to efforts in reducing that risk.